EFEKTIVITAS PENDIDIKAN GIZI DENGAN APLIKASI BERBASIS ANDROID TERHADAP PENGETAHUAN SERTA KONSUMSI SAYUR DAN BUAH REMAJA - Salsabilla Fauziah; Surmita Surmita; Witri Priawantiputri; Mira Mutiyani; Umi Mahmudah; Gurid Mulyo (Jurnal Gizi dan Dietetik, 2023)
One of many eating behavior problems is the lack of vegetables and fruit consumption. The lack of knowledge decrease personal ability in implementing the nutritional information in daily life. Nutrition Education is one of the effort to overcome the vegetable and fruit consumption problem. This study aims to see the effect of Nutrition Education using Android based application "My Food Record" media for the vegetable and fruit consumption and knowledge to the teenager in SMPN 8 Cimahi. The study design was Quasi-Experimental using pretest and posttest with control group of purposive sampling, each group consist of 20 people. The average score of Vegetable and fruit knowlede achieved before intervention is 40.33 and after intervention is 48.00. The average vegetable consumption per day before intervention is 108.93gr while after intervention is 123.12gr. In addition, the average fruit consumption per day before intervention is 294.23gr and after intervention is 341.86gr. T-test and Wilcoxon test show there is a significant effect on Vegetable and Fruit Knowledge (p=0.000 and 0.0008), meanwhile there is no significant effect on the Vegetable (p=0.600 and 0.811) and Fruit (p=0.802) consumption on both groups. The result of independent test, T-test and Mann Whitney shows no significant different of average vegetable and fruit knowledge (p=0.348), vegetable consumption (p=0.477), and fruit consumption (p=0949). The nutrition Education is able to increase the vegetable and fruit knowledge and consumption eventhough it is not statistically significant. Nutrition education of fruit and vegetable using this android based application needs a continuation to achieve the knowledge upgrade and positive behavior change.